Three new records of Aroids (Araceae) for Bangladesh - Ara, Hosne; Hassan, Md Abul (Bangladesh Journal of Plant Taxonomy, 2006)
Three aroid species, namely Colocasia gigantea (Blume) Hook. f., Epipremnum pinnatum (L.) Engl. and Scindapsus perakensis Hook. f. under the family Araceae are recorded for the first time for Bangladesh. An updated nomenclature including important synonyms, illustrated descriptions, flowering and fruiting times, specimens examined, ecology, geographical distribution, occurrance within Bangladesh and uses for each species have also been provided. Key words: Colocasia gigantea, Epipremnum pinnatum, Scindapsus perakensis, New records, Araceae, Bangladesh DOI: 10.3329/bjpt.v13i2.581 Bangladesh J. Plant Taxon. 13(2): 83-91, 2006 (December)